Back Cover: ASBase: Aggregates of fluorescent gels assembled by interfacial dynamic bonds. Issue 2 (24th April 2023) - Hu, Ziqing; Xu, Shaoyu; Zhang, Hanwei; Ji, Xiaofan
Abstract : Researches on both microscopic and macroscopic aggregates are significant, whereas, most studies of aggregates have focused on microscopic building blocks. Fluorescent gels, as the important macroscopic building blocks, show extraordinary fluorescence and soft material properties. Herein, Ji and co‐workers summarized a series of aggregates of fluorescent gels based on interfacial non‐covalent bonds and dynamic covalent bonds (e283 ).